Usefulness of a mobile app to improve performance of specialists in responding correctly to CRC screening and surveillance clinical scenarios - Pereyra, Lisandro; Steinberg, Leandro; Criniti, Juan M.; Luna, Pablo; Escobar, Rafael; Bun, Maximiliano; Yantorno, Martín; Esteves, Sebastian; Gonzalez, Nicolas; Hoffman, Pablo; Marcolongo, Mariano; Jury, Gastón; Topor, Javier; Trelles, Félix; Nazar, Cristina; Arantes, Vitor N. (Endoscopy International Open, 2021)
Background and study aims The adherence to and knowledge of physicians about colorectal cancer (CRC) screening and surveillance guidelines is still suboptimal, threatening the effectiveness of CRC screening. This study assessed the usefulness of a mobile decision support system (MDSS) to improve physician ability to recommend proper timing of and intervals for CRC screening and surveillance.Patients and methods This was a binational, single-blinded, randomized clinical trial including gastroenterologists and colorectal surgeons from Argentina and Uruguay. The specialists were invited to respond to a questionnaire with 10 CRC screening and surveillance clinical scenarios, randomized into two groups, with and without access to a dedicated app (CaPtyVa). The main outcome measure was the proportion of physicians correctly solving at least 60 % of the clinical cases according to local guidelines.Results A total of 213 physicians were included. The proportion of physicians responding correctly at least 60 % of the vignettes was higher in the app group as compared to the control group (90 % versus 56 %) (relative risk [RR] 1.6 95 % confidence interval [CI] 1.34–1.91). The performance was also higher in the app group for both vignette categories: CRC screening (93 % vs 75 % RR 1.24, 95 %CI 1.01–1.40) and surveillance (85 % vs 47 % RR 1.81 95 %CI 1.46–2.22), respectively. Physicians considered the app easy to use and of great utility in daily practice.Conclusions A MDSS was shown to be a useful tool that improved specialist performance in solving CRC screening and surveillance clinical scenarios. Its implementation in daily practice may facilitate the adherence of physicians to CRC screening and surveillance guidelines.